A triptolide preparation and preparation method thereof
By loading triplet methylcin in drug-loaded nanocarbons and encapsulated in alcohol bodies, the problems of poor water solubility and great toxicity of triplet methylcin were solved, and the effect of rapid onset and sustained release of transdermal administration was achieved, which improved the bioavailability and safety of the drug.
Patent Information
- Application Number
- CN202411261858.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The defects of triptylenol have poor water solubility, certain toxicity, similar treatment concentration to poisoning concentration, and rapid elimination in the body have hindered its widespread application in clinical practice.
A transdermal preparation of triptium administered by loading triptium on drug-loaded nanocarbons and encapsulating it in alcohol bodies, and using microneedle mold molding and polyvinyl alcohol solution coating were prepared.
This preparation can achieve rapid onset and sustained release efficacy, reduce digestive tract toxicity, avoid first pass effect, improve the bioavailability of the drug and skin transmittance, and reduce the toxic and side effects of the drug.
Smart Images

Figure BDA0005035934110000111 
Figure BDA0005035934110000132
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pharmaceutical preparations, and particularly relates to a triptolide preparation and a preparation method thereof. Background Art
[0002] Triptolide is an epoxidized diterpene lactone compound isolated from Tripterygium wilfordii, a plant of the Celastraceae family. It has been used as an anti-inflammatory drug to treat a variety of kidney diseases. However, triptolide has poor water solubility, certain toxicity, a therapeutic concentration close to the toxic concentration, and rapid elimination from the body, which hinders its clinical application. Therefore, it is very necessary to construct a biocompatible kidney-specific drug delivery platform to effectively utilize triptolide. Ethosomes, as a new generation of liposomes, are drug delivery carriers with vesicle structures composed of phospholipids, high volume fraction ethanol, etc. and water. Compared with ordinary liposomes, they have a stable structure, a higher encapsulation rate, and better membrane fluidity, which allows drugs to pass through the stratum corneum or mucosal cells of the skin, with higher bioavailability. They are good skin and mucosal drug delivery carriers with good application prospects. Summary of the invention
[0003] The present invention mainly provides a transdermal triptolide preparation with rapid onset, sustained release and few side effects. The technical scheme is as follows:
[0004] A triptolide preparation comprises drug-loaded nano-carbon loaded with triptolide and an ethosome wrapped around the drug-loaded nano-carbon.
[0005] Furthermore, the alcohol body wrapped with the drug-loaded nanocarbon is molded using a microneedle mold, and then coated with a polyvinyl alcohol solution, and dried to obtain.
[0006] Furthermore, the nanocarbon includes one or more of carbon nanotubes, carbon nanofibers or carbon nanospheres.
[0007] A method for preparing the above-mentioned triptolide preparation comprises the following steps:
[0008] a. Carboxyl-modifying the nanocarbon so that the surface of the nanocarbon carries a large number of carboxyl groups;
[0009] b. After chitosan oligosaccharide is soaked in anhydrous ethanol to swell, modified nanocarbon and catalyst are added, and the reaction is stirred at 60-70°C for 8-10 hours; the reaction solution is added dropwise into acetone while stirring, and after standing for 0.5-2 hours, the precipitate is collected and fully washed with acetone, and freeze-dried to obtain a chitosan oligosaccharide nanocarbon composite;
[0010] c. Place triptolide in ethanol to obtain a 3-5 mg / mL triptolide ethanol solution; disperse the chitosan oligosaccharide nanocarbon complex in water to obtain a dispersion, and then slowly drip the triptolide ethanol solution into the dispersion. After sufficient dispersion, stir at 40-60° C. until there is no obvious water mark in the container to obtain drug-loaded nanocarbon;
[0011] d. The drug-loaded nanocarbon is fully dispersed in glycerol to obtain a paste-like dispersion, and the dispersion is fully solidified at below 10°C, then ground and maintained in a solid state; soybean lecithin, cholesterol and anhydrous ethanol are fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, the ground dispersion is sieved into the matrix solution while stirring, and after sufficient mixing, ultrasonic treatment is performed for 3 to 10 minutes, and the solid is collected.
[0012] Furthermore, in step b, the mass ratio of chitosan oligosaccharide to nanocarbon is 1:1.2-2.5; the mass ratio of the catalyst to chitosan oligosaccharide is 1:4-6.
[0013] Furthermore, the catalyst in step b includes one of 3A molecular sieve, 4A molecular sieve, 5A molecular sieve or 13X molecular sieve.
[0014] Furthermore, the mass ratio of triptolide to chitosan oligosaccharide nano-carbon composite in step c is 1:10-15; and the speed of slow dripping in step c is 0.05-0.3 mL / s.
[0015] Furthermore, the ultrasonic treatment in step d is carried out at 250W, 40kHz; the mass ratio of the drug-loaded nanocarbon to glycerol in step d is 1:1.2-1.5; the mass ratio of the glycerol to anhydrous ethanol is 1:3-5; the mass ratio of the cholesterol, lecithin and anhydrous ethanol is 1:5:3-4.
[0016] Furthermore, the step a of carboxyl-modifying the nanocarbon comprises the following steps: placing the nanocarbon in a mixed acid of concentrated sulfuric acid and concentrated nitric acid, mixing evenly, refluxing at 80° C. for 3 h, cooling to room temperature and then diluting with water, standing overnight, pouring out the supernatant, and then adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon.
[0017] Furthermore, the volume ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid is 3:1.
[0018] By adopting the above scheme, the method of the present invention has the following advantages:
[0019] 1. In the preparation of the present invention, triptolide is loaded on nanocarbon and then wrapped by ethosomes. After transdermal administration, it can reduce gastrointestinal toxicity and avoid first-pass effect, and can also slowly and continuously exert its therapeutic effect through the skin. It has a high drug loading rate and a high skin permeability.
[0020] 2. The preparation of the present invention has a stable structure, a high encapsulation rate, a small particle size, and a higher bioavailability. Through the microneedle, triptolide can penetrate the stratum corneum or mucosal cells of the skin, release the drug when penetrating the cells, and allow the drug to penetrate into the deeper layers of the skin, so that it has a larger retention amount in the dermis of the skin, thereby improving the drug transdermal efficiency.
[0021] 3. The present invention loads the triptolide drug on nanocarbon, and slowly releases the drug after entering deep into the skin, thereby avoiding the toxic side effects caused by large-scale intake of triptolide, and solving the problem that the effective dose of triptolide is close to the toxic dose.
[0022] 4. The present invention uses oligochitosan and nanocarbon to improve the active sites of the carrier and the drug compatibility, so that the affinity of nanocarbon and triptolide is stronger, the cross-linking ability of the oligochitosan nanocarbon complex and triptolide is stronger, and the drug loading capacity is increased.
[0023] 5. In the preparation of the alcohol body, the present invention uses glycerol to combine with the drug-loaded nanocarbon, and utilizes the phase change of glycerol to improve the dispersion of the drug-loaded nanocarbon and the matrix, so that the coating is more uniform and complete. In the process of forming the alcohol body, the inner core of the drug-loaded nanocarbon has a slight change in volume due to the melting of glycerol, which makes the combination of the alcohol body and the drug-loaded nanocarbon more firmly. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Embodiment 1:
[0026] (1) placing the nanocarbon spheres in a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, mixing evenly, reflux at 80°C for 3h, cooling to room temperature and diluting with water, standing overnight, pouring out the supernatant, adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon;
[0027] (2) After 400 mg of chitosan oligosaccharide was soaked in anhydrous ethanol to swell, 0.48 g of nanocarbon and 80 mg of 5A molecular sieve were added, and the mixture was stirred at 65° C. for 9 h; the reaction solution was added dropwise into acetone while stirring, and after standing for 1 h, the precipitate was collected and fully washed with acetone, and freeze-dried to obtain a chitosan oligosaccharide nanocarbon composite;
[0028] (3) 5 mg of triptolide was placed in ethanol to obtain a 4 mg / mL triptolide ethanol solution; 50 mg of chitosan oligosaccharide nanocarbon complex was dispersed in water to obtain a dispersion, and then the triptolide ethanol solution was slowly dripped into the dispersion at a rate of 0.05 mL / s. After sufficient dispersion, it was stirred at 50° C. until there was no obvious water mark in the container, thereby obtaining drug-loaded nanocarbon;
[0029] (4) The drug-loaded nanocarbon obtained in step (3) is placed in 6 mg of glycerol and fully dispersed to obtain a paste-like dispersion, and the dispersion is fully solidified at below 10° C., then ground and maintained in a solid state; 1 mg of cholesterol, 5 mg of soybean lecithin and 15 mg of anhydrous ethanol are taken and fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, the ground dispersion is sieved into the matrix solution while stirring, and after sufficient mixing, 250 W, 40 kHz ultrasonic treatment is performed for 3 to 10 min, and the solid is collected.
[0030] Embodiment 2:
[0031] (1) placing the nanocarbon spheres in a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, mixing evenly, reflux at 80°C for 3h, cooling to room temperature and diluting with water, standing overnight, pouring out the supernatant, adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon;
[0032] (2) After 400 mg of chitosan oligosaccharide was soaked in anhydrous ethanol to swell, 1 g of nanocarbon and 80 mg of 5A molecular sieve were added, and the mixture was stirred at 65° C. for 9 h; the reaction solution was added dropwise into acetone while stirring, and after standing for 1 h, the precipitate was collected and fully washed with acetone, and freeze-dried to obtain a chitosan oligosaccharide nanocarbon composite;
[0033] (3) 5 mg of triptolide was placed in ethanol to obtain a 4 mg / mL triptolide ethanol solution; 50 mg of chitosan oligosaccharide nanocarbon complex was dispersed in water to obtain a dispersion, and then the triptolide ethanol solution was slowly dripped into the dispersion at a rate of 0.05 mL / s. After sufficient dispersion, it was stirred at 50° C. until there was no obvious water mark in the container, thereby obtaining drug-loaded nanocarbon;
[0034] (4) The drug-loaded nanocarbon obtained in step (3) is placed in 6 mg of glycerol and fully dispersed to obtain a paste-like dispersion, and the dispersion is fully solidified at below 10° C., then ground and maintained in a solid state; 1 mg of cholesterol, 5 mg of soybean lecithin and 15 mg of anhydrous ethanol are taken and fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, the ground dispersion is sieved into the matrix solution while stirring, and after sufficient mixing, 250 W, 40 kHz ultrasonic treatment is performed for 3 to 10 min, and the solid is collected.
[0035] Embodiment 3:
[0036] (1) placing the nanocarbon spheres in a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, mixing evenly, reflux at 80°C for 3h, cooling to room temperature and diluting with water, standing overnight, pouring out the supernatant, adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon;
[0037] (2) After 400 mg of chitosan oligosaccharide was soaked in anhydrous ethanol to swell, 0.48 g of nanocarbon and 80 mg of 5A molecular sieve were added, and the mixture was stirred at 65° C. for 9 h; the reaction solution was added dropwise into acetone while stirring, and after standing for 1 h, the precipitate was collected and fully washed with acetone, and freeze-dried to obtain a chitosan oligosaccharide nanocarbon composite;
[0038] (3) 5 mg of triptolide was placed in ethanol to obtain a 4 mg / mL triptolide ethanol solution; 75 mg of chitosan oligosaccharide nanocarbon complex was dispersed in water to obtain a dispersion, and then the triptolide ethanol solution was slowly dripped into the dispersion at a rate of 0.05 mL / s. After sufficient dispersion, it was stirred at 50° C. until there was no obvious water mark in the container, thereby obtaining drug-loaded nanocarbon;
[0039] (4) The drug-loaded nanocarbon obtained in step (3) is placed in 6 mg of glycerol and fully dispersed to obtain a paste-like dispersion, and the dispersion is fully solidified at below 10° C., then ground and maintained in a solid state; 1 mg of cholesterol, 5 mg of soybean lecithin and 15 mg of anhydrous ethanol are taken and fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, the ground dispersion is sieved into the matrix solution while stirring, and after sufficient mixing, 250 W, 40 kHz ultrasonic treatment is performed for 3 to 10 min, and the solid is collected.
[0040] Embodiment 4:
[0041] (1) placing the nanocarbon spheres in a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, mixing evenly, reflux at 80°C for 3h, cooling to room temperature and diluting with water, standing overnight, pouring out the supernatant, adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon;
[0042] (2) After 400 mg of chitosan oligosaccharide was soaked in anhydrous ethanol to swell, 0.48 g of nanocarbon and 80 mg of 5A molecular sieve were added, and the mixture was stirred at 65° C. for 9 h; the reaction solution was added dropwise into acetone while stirring, and after standing for 1 h, the precipitate was collected and fully washed with acetone, and freeze-dried to obtain a chitosan oligosaccharide nanocarbon composite;
[0043] (3) 5 mg of triptolide was placed in ethanol to obtain a 4 mg / mL triptolide ethanol solution; 50 mg of chitosan oligosaccharide nanocarbon complex was dispersed in water to obtain a dispersion, and then the triptolide ethanol solution was slowly dripped into the dispersion at a rate of 0.3 mL / s. After sufficient dispersion, it was stirred at 50° C. until there was no obvious water mark in the container, thereby obtaining drug-loaded nanocarbon;
[0044] (4) The drug-loaded nanocarbon obtained in step (3) is placed in 6 mg of glycerol and fully dispersed to obtain a paste-like dispersion, and the dispersion is fully solidified at below 10° C., then ground and maintained in a solid state; 1 mg of cholesterol, 5 mg of soybean lecithin and 15 mg of anhydrous ethanol are taken and fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, the ground dispersion is sieved into the matrix solution while stirring, and after sufficient mixing, 250 W, 40 kHz ultrasonic treatment is performed for 3 to 10 min, and the solid is collected.
[0045] Embodiment 5:
[0046] (1) placing the nanocarbon spheres in a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, mixing evenly, reflux at 80°C for 3h, cooling to room temperature and diluting with water, standing overnight, pouring out the supernatant, adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon;
[0047] (2) After 400 mg of chitosan oligosaccharide was soaked in anhydrous ethanol to swell, 0.48 g of nanocarbon and 80 mg of 5A molecular sieve were added, and the mixture was stirred at 65° C. for 9 h; the reaction solution was added dropwise into acetone while stirring, and after standing for 1 h, the precipitate was collected and fully washed with acetone, and freeze-dried to obtain a chitosan oligosaccharide nanocarbon composite;
[0048] (3) 5 mg of triptolide was placed in ethanol to obtain a 4 mg / mL triptolide ethanol solution; 50 mg of chitosan oligosaccharide nanocarbon complex was dispersed in water to obtain a dispersion, and then the triptolide ethanol solution was slowly dripped into the dispersion at a rate of 0.05 mL / s. After sufficient dispersion, it was stirred at 50° C. until there was no obvious water mark in the container, thereby obtaining drug-loaded nanocarbon;
[0049] (4) The drug-loaded nanocarbon obtained in step (3) is placed in 7.5 mg of glycerol and fully dispersed to obtain a paste-like dispersion, and the dispersion is fully solidified at below 10° C., then ground and maintained in a solid state; 1 mg of cholesterol, 5 mg of soybean lecithin and 15 mg of anhydrous ethanol are taken and fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, the ground dispersion is sieved into the matrix solution while stirring, and after fully mixing, 250 W, 40 kHz ultrasonic treatment is performed for 3 to 10 min, and the solid is collected.
[0050] Embodiment 6:
[0051] (1) placing the nanocarbon spheres in a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, mixing evenly, reflux at 80°C for 3h, cooling to room temperature and diluting with water, standing overnight, pouring out the supernatant, adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon;
[0052] (2) After 400 mg of chitosan oligosaccharide was soaked in anhydrous ethanol to swell, 0.48 g of nanocarbon and 80 mg of 5A molecular sieve were added, and the mixture was stirred at 65° C. for 9 h; the reaction solution was added dropwise into acetone while stirring, and after standing for 1 h, the precipitate was collected and fully washed with acetone, and freeze-dried to obtain a chitosan oligosaccharide nanocarbon composite;
[0053] (3) 5 mg of triptolide was placed in ethanol to obtain a 4 mg / mL triptolide ethanol solution; 50 mg of chitosan oligosaccharide nanocarbon complex was dispersed in water to obtain a dispersion, and then the triptolide ethanol solution was slowly dripped into the dispersion at a rate of 0.05 mL / s. After sufficient dispersion, it was stirred at 50° C. until there was no obvious water mark in the container, thereby obtaining drug-loaded nanocarbon;
[0054] (4) The drug-loaded nanocarbon obtained in step (3) is placed in 6 mg of glycerol and fully dispersed to obtain a paste-like dispersion, and the dispersion is fully solidified at below 10° C., then ground and maintained in a solid state; 1 mg of cholesterol, 5 mg of soybean lecithin and 20 mg of anhydrous ethanol are taken and fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, the ground dispersion is sieved into the matrix solution while stirring, and after sufficient mixing, 250 W, 40 kHz ultrasonic treatment is performed for 3 to 10 min, and the solid is collected.
[0055] Comparative Example 1:
[0056] (1) placing the nanocarbon spheres in a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, mixing evenly, reflux at 80°C for 3h, cooling to room temperature and diluting with water, standing overnight, pouring out the supernatant, adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon;
[0057] (2) After 400 mg of chitosan oligosaccharide was soaked in anhydrous ethanol to swell, 0.48 g of nanocarbon and 80 mg of 5A molecular sieve were added, and the mixture was stirred at 65° C. for 9 h; the reaction solution was added dropwise into acetone while stirring, and after standing for 1 h, the precipitate was collected and fully washed with acetone, and freeze-dried to obtain a chitosan oligosaccharide nanocarbon composite;
[0058] (3) 5 mg of triptolide was placed in ethanol to obtain a 4 mg / mL triptolide ethanol solution; 50 mg of chitosan oligosaccharide nanocarbon complex was dispersed in water to obtain a dispersion, and then the triptolide ethanol solution was slowly dripped into the dispersion at a rate of 0.05 mL / s. After sufficient dispersion, it was stirred at 50° C. until there was no obvious water mark in the container, thereby obtaining drug-loaded nanocarbon;
[0059] (4) The drug-loaded nanocarbon obtained in step (3) is placed in 6 mg of glycerol and fully dispersed to obtain a paste-like dispersion; 1 mg of cholesterol, 5 mg of soybean lecithin and 15 mg of anhydrous ethanol are taken and fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, slowly add the matrix solution while stirring, after fully mixing, ultrasonically treat at 250 W, 40 kHz for 3 to 10 min, and collect the solid.
[0060] Comparative Example 2:
[0061] (1) placing the nanocarbon spheres in a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, mixing evenly, reflux at 80°C for 3h, cooling to room temperature and diluting with water, standing overnight, pouring out the supernatant, adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon;
[0062] (2) 5 mg of triptolide was placed in ethanol to obtain a 4 mg / mL triptolide ethanol solution; 50 mg of modified nanocarbon was dispersed in water to obtain a dispersion, and then the triptolide ethanol solution was slowly dripped into the dispersion at a rate of 0.05 mL / s. After sufficient dispersion, it was stirred at 50° C. until there was no obvious water mark in the container, thereby obtaining drug-loaded nanocarbon;
[0063] (3) The drug-loaded nanocarbon obtained in step (2) is placed in 6 mg of glycerol and fully dispersed to obtain a paste-like dispersion, and the dispersion is fully solidified at below 10° C., then ground and maintained in a solid state; 1 mg of cholesterol, 5 mg of soybean lecithin and 15 mg of anhydrous ethanol are taken and fully mixed and dissolved to obtain a matrix solution; at a speed of 100 to 300 rpm, the ground dispersion is sieved into the matrix solution while stirring, and after fully mixing, 250 W, 40 kHz ultrasonic treatment is performed for 3 to 10 min, and the solid is collected.
[0064] Preparation and testing of samples of the embodiments:
[0065] After re-dissolving the samples of each embodiment and comparative example in methanol, centrifuge at a speed of 15000 rpm for 15 min, take the supernatant, add methanol to break the emulsion into a 5 mL volumetric flask, filter with a 0.22 μm microporous filter membrane, and use a high performance liquid chromatograph for sample injection and determination. The encapsulation efficiency is calculated by the ratio of the difference between the total drug amount and the free drug amount to the total drug amount.
[0066] The results are as follows:
[0067]
[0068] As can be seen from the above table, compared with Example 1, the encapsulation rate of Example 2, which adds more modified nano-carbon and chitosan oligosaccharide composites, increases, indicating that when the content of chitosan oligosaccharide is constant, more modified nano-carbon is conducive to the full composite of chitosan oligosaccharide and nano-carbon. Comparative Example 2 does not use chitosan oligosaccharide for composite, but directly uses modified nano-carbon for loading, and the encapsulation rate decreases significantly, indicating that the composite of oligochitosan has a significant improvement effect on the loading capacity of nano-carbon and the affinity with triptolide. The encapsulation rate of Example 3 with a higher content of chitosan oligosaccharide nano-carbon composites has a significant increase. The encapsulation rate of Example 4 has decreased, indicating that when triptosan oligosaccharide is mixed with chitosan oligosaccharide nano-carbon composites, a lower drop rate is conducive to the loading of triptosan oligosaccharide and chitosan oligosaccharide nano-carbon composites. The encapsulation rates of Example 5 and Example 6 have decreased slightly, but the decrease is not obvious, indicating that in the process of preparing alcohol body, the ratio between substances will affect the encapsulation capacity of alcohol body, but the influence within a reasonable range is not large. In comparative example 1, glycerol was not solidified during the preparation of ethosomes, and the encapsulation efficiency decreased significantly, indicating that the solidification process was conducive to the firm loading of the drug.
[0069] The in vitro transdermal diffusion test was carried out using a Franz diffusion cell. The intact rat skin was taken, and 30% ethanol saline was taken as the receiving solution. The rat skin was spread on the Franz diffusion cell and contacted with the drug supply layer. The bubbles in the device were discharged, and the device was sealed and placed in a water bath in a pool with a stirring speed of 300 rpm and a temperature set to (37±0.5)°C to activate the skin for more than 30 minutes; 1 mL of the solution of each embodiment and comparative example containing 5 mg of triptolide was prepared and administered, and 2.5 mL of liquid was taken out from the receiving cell at 1, 2, 4, 6, 8, 10, 12, and 24 hours, respectively, and then an equal volume of receiving solution was added; after 24 hours, the rat's administered skin was taken out, the skin surface was wiped clean, and then cut into pieces, an appropriate amount of methanol was added, ultrasonically extracted for 15 minutes, placed in a centrifuge tube, and centrifuged at 15000 rpm for 15 minutes, the supernatant was taken, and the sample was filtered with a 0.22 μm microporous filter membrane. The filtrate was injected using a high performance liquid chromatograph to determine the concentration of triptolide, and the formula was used. Calculate the skin retention per unit area. n is the cumulative permeation amount of the drug per unit area, C n is the concentration of triptolide at sampling time point n, V r is the volume of the receiving tank, C i is the concentration of triptolide at the time point before sampling time point t, V s is the sampling volume each time, and A is the effective transdermal area.
[0070]
[0071] As can be seen from the table above, the cumulative permeation of Example 2 containing more nanocarbon and Example 3 containing more chitosan oligosaccharide nanocarbon composites are significantly increased. The nanocarbon-based composite is conducive to the release of triptolide, and the skin penetration ability is stronger. The permeability of Example 3 with more chitosan oligosaccharide nanocarbon composites is significantly increased compared with Example 2, indicating that compared with the increase in the amount of a single substance, the combination of chitosan oligosaccharide and nanocarbon can synergistically increase the penetration of the preparation. The cumulative permeation of Example 5, which adds more glycerol to participate in the formation of ethosomes, also increases, indicating that the participation of glycerol in the formation of liposomes can increase skin penetration.
[0072] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a triptolide preparation, characterized in that: The triptolide preparation comprises a drug-loaded nanocarbon loaded with triptolide and an ethosome wrapped with the drug-loaded nanocarbon; the preparation method comprises the following steps: a. Carboxyl-modifying the nanocarbon so that the surface of the nanocarbon carries a large number of carboxyl groups to obtain modified nanocarbon; b. Soak the chitosan oligosaccharide in anhydrous ethanol to swell, add the modified nanocarbon and catalyst, and stir the reaction at 60-70°C for 8-10 hours; add the reaction solution dropwise into acetone while stirring, let it stand for 0.5-2 hours, collect the precipitate, wash it thoroughly with acetone, and freeze-dry it to obtain the chitosan oligosaccharide nanocarbon composite; c. Place triptolide in ethanol to obtain a 3-5 mg / mL triptolide ethanol solution; disperse the chitosan oligosaccharide nanocarbon complex in water to obtain a dispersion; then slowly drip the triptolide ethanol solution into the dispersion, and after sufficient dispersion, stir at 40-60°C until there is no obvious water mark in the container to obtain drug-loaded nanocarbon; d. Disperse the drug-loaded nanocarbon in glycerol to obtain a paste-like dispersion, fully solidify the dispersion at a temperature below 10°C, and then grind and maintain the solid state; fully mix and dissolve soybean lecithin, cholesterol and anhydrous ethanol to obtain a matrix solution; sieve the grinded dispersion into the matrix solution while stirring at a speed of 100-300 rpm, fully mix, and ultrasonically treat for 3-10 minutes to collect the solid.
2. The method for preparing the triptolide preparation according to claim 1, characterized in that: The alcohol body wrapped with the drug-loaded nanocarbon is molded by using a microneedle mold, and then coated with a polyvinyl alcohol solution, and dried to obtain.
3. The method for preparing the triptolide preparation according to claim 1, characterized in that: The nanocarbon includes one or more of carbon nanotubes, carbon nanofibers or carbon nanospheres.
4. The method for preparing the triptolide preparation according to claim 1, characterized in that: In step b, the mass ratio of the chitosan oligosaccharide to the modified nanocarbon is 1:1.2-2.5; the mass ratio of the catalyst to the chitosan oligosaccharide is 1:4-6.
5. The method for preparing the triptolide preparation according to claim 1, characterized in that: The catalyst in step b comprises one of 3A molecular sieve, 4A molecular sieve, 5A molecular sieve or 13X molecular sieve.
6. The method for preparing the triptolide preparation according to claim 1, characterized in that: The mass ratio of triptolide to chitosan oligosaccharide nano-carbon complex in step c is 1:10-15; the speed of slow dripping in step c is 0.05-0.3 mL / s.
7. The method for preparing the triptolide preparation according to claim 1, characterized in that: The ultrasonic treatment in step d is carried out at 250W and 40kHz; the mass ratio of the drug-loaded nanocarbon to glycerol in step d is 1:1.2-1.5; the mass ratio of the glycerol to anhydrous ethanol is 1:3-5; and the mass ratio of the cholesterol, lecithin and anhydrous ethanol is 1:5:3-4.
8. The method for preparing the triptolide preparation according to claim 1, characterized in that: The step a of carboxyl-modifying the nanocarbon comprises the following steps: placing the nanocarbon in a mixed acid of concentrated sulfuric acid and concentrated nitric acid, mixing evenly, refluxing at 80° C. for 3 h, cooling to room temperature and then diluting with water, standing overnight, pouring out the supernatant, and then adding an appropriate amount of distilled water to neutralize the mixed acid, filtering, washing the filter cake with water until it is neutral, and fully drying to obtain modified nanocarbon.
9. The method for preparing the triptolide preparation according to claim 8, characterized in that: The volume ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid is 3:1.
Citation Information
Patent Citations
Triptolide liposome preparation for treatment of small cell lung cancer and preparation method thereof
CN103393598A
Breast cancer treatment triptolide liposome preparation and preparation method thereof
CN103462898A